To solve for y, we need to isolate y on one side of the equation.
Starting with the equation:
-31 = -39 - y/8
First, let's get rid of the fraction by multiplying every term in the equation by 8:
8*(-31) = 8*(-39) - 8*(y/8)
Simplifying this gives us:
-248 = -312 - y
Now, let's isolate y by adding 312 to both sides of the equation:
-248 + 312 = -312 - y + 312
Simplifying further:
64 = -y
To solve for y, we can multiply both sides by -1 to get rid of the negative:
-1 * 64 =-1 * -y
This simplifies to:
-64 = y
Therefore, the solution is y = -64.
solve for y
-31= -39 - y/8
1 answer